Digital Platforms and Right to Information: From Mere Hosts to Responsible Actors - Basanta Vázquez, Blanca (2025)
Despite the apparent neutrality of digital platforms, they exert a significant influence on the mediation of information, which raises questions about their responsibility to guarantee the right to information and democratic sustainability. This article analyses the intermediary role of digital platforms, considering that their presence has transformed the model of public communication. Taking as a starting point Desantes' (1994) defence of information as a human and social good, which engenders a duty for those who issue it, this research argues that digital platforms, like media, must assume a structural responsibility with information. This article explores, through a discussion with the ideas of the main theorists, how platforms have altered public communication, challenging traditional principles of the media and underlining the need to demand operational responsibility from them, as has been done by recent EU regulation.